Institutional and large-scale learning assessment in the school context (Research, Society and Development, 2022)
The systematic approach to the evaluation of learning, institutional on a wide scale, plans to analyze what has been indicated in this triadic perspective in the school context, since the methodological instruments must in this way cross such an evaluative purpose. In this way, we will operate with the statement of evaluation in relation to the evaluation of learning, institutional and broad scale after all, you want to measure learning in a micro and macro dimension. The main question is what is the purpose of the evaluation in the school context? We aim to identify the deployment of the evaluation in the school context as a tool to promote the development and strengthening of the institution that is dedicated to educating for a certain purpose, understand the functions of evaluation in the school context and problematize the purpose of evaluation on a wide scale as well as the institutional one. As findings, we can point out that learning evaluation aims at student learning, institutional evaluation, institution development and wide-scale evaluation corroborates with the Índice de Desenvolvimento da Educação Básica (IDEB), which measures quality of Education.